Non-normal distribution of the top-of-atmosphere satellite optical measurements over calibration sites. Issue 19 (1st October 2016) - Gorroño, Javier; Bialek, Agnieszka; Green, Paul D.; Harris, Peter; Scanlon, Tracy; Fox, Nigel P.; Underwood, Craig
ABSTRACT: This paper studies the distribution associated with the measurement of the satellite-derived top-of-atmosphere (TOA) reflectance on a pixel-to-pixel level, within a defined spatial region of interest (ROI) within a vicarious calibration target site. The study analyses the effects of the atmosphere and surface reflectance distribution spatial shape. The analysis shows that some of the contributing effects are inherently nonlinear, so produce non-normal distributions. For these non-normal distributions, the use of the mean and standard deviation alone does not allow sufficient parameterization of the distribution to capture all the information associated with the ROI reflectance measurement. Therefore, additional information concerning the distribution is required to provide a full site reflectance characterization. This additional information can be useful in establishing the sources of change in the distribution and ultimately improve the site radiometric characterization, particularly for long-term monitoring. In this study, Landsat-8 (L8) Operational Land Imager (OLI) measurements over the CEOS Libya-4 Pseudo Invariant Calibration Site (PICS) are used as a demonstration.